Facultar al notario celebrar matrimonio civil y mediación de hijos dependientes en divorcios voluntarios - Sánchez García, Johanna Catalina (2026)
The objective of the study is to develop a critical legal analysis of the power of the notary to perform civil marriages and mediation of dependent children in voluntary divorces. In order to fulfill this objective, it was necessary to use a qualitative research approach, also using methods such as analytical, descriptive and comparative with countries of Colombia and Peru. The tool used was the interview of notaries and legal professionals specialized in civil and procedural law. Among the most important analyses are that in Ecuador notaries are vested with public faith, which empowers them to celebrate acts of voluntary jurisdiction in order to decongest the Civil Registry and offer citizens a fast service that complies with the principles of simplicity, speed and procedural economy. Therefore, the parties are the ones who must choose where they wish to carry out the voluntary divorce either before a notary or the Civil Registry. Therefore, it can be concluded that voluntary divorce complies with a constitutional mandate indicated in Art. 169, which refers to the fact that justice must comply with the principles of simplification, celerity and procedural economy, without affecting the principle of due process.